Are We Replicating Yet? Reproduction and Replication in Communication Research - Breuer, Johannes (2024)
The replication crisis has highlighted the importance of reproducibility and replicability in the social and behavioral sciences, including in communication research. While there have been some discussions of and studies on replications in communication research, the extent of this work is significantly lower than in psychology. The key reasons for this limitation are the differences between the disciplines in the topics commonly studied and in the methods and data commonly used in communication research. Communication research often investigates dynamic topics and uses methods (e.g., content analysis) and data types (e.g., media content and social media data) that are not used, or, at least, are much less frequently used, in other fields. These specific characteristics of communication research must be considered and require a more nuanced understanding of reproducibility and replicability. This thematic issue includes commentaries presenting different perspectives, as well as methodological and empirical work investigating the reproducibility and replicability of a wide range of communication research, including surveys, experiments, systematic literature reviews, and studies that involve social media or audio data. The articles in this issue acknowledge the diversity and unique features of communication research and present various ways of improving its reproducibility and replicability, as well as our understanding thereof.